PENGARUH PAKET EDUKASI SAYANG IBU TERHADAP MOTIVASI IBU DALAM PEMBERIAN ASI EKSKLUSIF DI KABUPATEN PEKALONGAN - Yuni Sandra Pratiwi; Siti Rofiqoh; Herni Rejeki (LPPM STIKES Muhammadiyah Kendal, 2019)
The low milk supply to infants is a very serious threat to the growth and development of infants as the next generation of the nation. Good motivation and ability will increase the role of mothers in giving milk to babies, so that breastfeeding to babies will increase. This study aims to identify the effect of the education package for maternal affection towards maternal motivation in exclusive breastfeeding. A quasi-experimental research method with a non-equivalent control group pre and post test approach. The research site is in the work area of ​​Buaran and Wonokerto 2 Public Health Centers in Pekalongan Regency with three trimester primigravida respondents. The sampling technique used consecutive sampling consisting of 38 respondents. Statistical tests using the Chi Square Test. The results of the study showed that there was an influence of the mother's love education package on mother's motivation in breastfeeding in the intervention group (p <0.05). Health workers are expected to be more active in health promotion programs, especially the education package for mothers to love pregnant women in order to increase the motivation of pregnant women in breastfeeding their babies. Keywords: ASI, Education, Motivation.